Problematic Pornography Use in Japan: A Preliminary Study Among University Students - Okabe, Yushun; Takahashi, Fumito; Ito, Daisuke (Frontiers in Psychology, 2021)
Background: Problematic pornography use is considered an addictive behavior, which is an important clinical issue. Despite considerable research interest in problematic pornography use worldwide, there has been no research on the subject in Japan. Objective: This is the first study in Japan focusing on the characteristics of problematic pornography use among Japanese students. Methods: The participants were 150 college students aged 20–26 years (mean age = 21.5, males: n = 86, females: n = 64) at a university in midland Japan. They completed an online questionnaire including items on pornography usage patterns, impaired control of pornography use, sexual compulsivity, depression, anxiety, and effortful control. Results: Most men (97%) and around one-third of women (35.9%) used pornography at least once in the past month. Some users reported significant daily-life problems (5.7%). Participants with impaired control of pornography use had high depression, anxiety, sexual compulsivity, and low effortful control than pornography users without impaired control. Conclusions: Some Japanese students reported significant daily-life problems due to impaired control of pornography use. The characteristics of individuals with impaired control are consistent with previous studies. The results of this study suggest that individuals with impaired control may have poor mental health, and there is a need for further research and developing treatment systems regarding this in Japan. Further research exploring a varied sample in Japan is required to effectively examine problematic pornography use.